2013
DOI: 10.2500/ajra.2013.27.3926
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Polyps

Abstract: Nasal polyps occur in 1-4% of the population, usually occurring in the setting of an underlying local or systemic disease. The most common associated condition is chronic rhinosinusitis (CRS). A high prevalence of nasal polyps is also seen in allergic fungal rhinosinusitis, aspirin-exacerbated respiratory disease, Churg-Strauss syndrome, and cystic fibrosis. In the setting of CRS, nasal polyps are not likely to be cured by either medical or surgical therapy; however, control is generally attainable. The best m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Prior evidence 22 , which was based on studies evaluating NP patients from Western countries, demonstrated that NPs was characterized by eosinophil infiltration and excessive Th2 cytokine expression. However, it is now recognized that polyp tissues from Chinese or Korean patients are biased toward neutrophilic inflammation and a significant increase in the Th1/Th17 cell pattern 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior evidence 22 , which was based on studies evaluating NP patients from Western countries, demonstrated that NPs was characterized by eosinophil infiltration and excessive Th2 cytokine expression. However, it is now recognized that polyp tissues from Chinese or Korean patients are biased toward neutrophilic inflammation and a significant increase in the Th1/Th17 cell pattern 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Nasal polyps are grape-shaped smooth structures, arising from the inflammatory nasal mucous membrane. Nasal polyps bulge to interior of the nose, restricting nasal patency [71]. There are different pathogenesis theories of nasal polyps, however, none was satisfactorily confirmed, and the lack of understanding nasal polyp pathogenesis impedes therapy.…”
Section: Lysosomes -Associated Diseases and Methods To Study Their Fumentioning
confidence: 99%
“…Since then, 20 other studies followed. Various challenges for this causal therapy remain unresolved and are subject of intense research (optimal gene transfer via the (modified) mucosal barrier, definition of the target cell, optimal gene expression rate, definition of meaningful outcome parameters) [ 132 ], [ 133 ], [ 134 ], [ 135 ], [ 136 ], [ 137 ], [ 138 ], [ 139 ], [ 140 ], [ 141 ], [ 142 ], [ 143 ].…”
Section: Disturbed Mucociliary Clearancementioning
confidence: 99%